Producing with sustainability: A study on circular practices in a rural property in Brazil - Sznitowski, Adelice Minetto; Queiroz, Adriane Angélica Farias Santos Lopes de; Padgett, Rosamaria Cox Moura Leite (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
The study aimed at identifying sustainable production practices on a rural property in Mato Grosso, Brazil from the perspective of the Circular Economy. The approach in the form of a single case study involved a location whose main activity is the production of grains and adopted qualitative data obtained through structured interviews with managers of the production units, observation and documentary research. The results show that, although sustainable production practices are adopted, there is room for advances. The study contributes by reporting sustainable production practices that can be related to circular agriculture, which has as the main goal the efficient and effective use of productive resources. At the end, 11 Circular Economy elements directed to agriculture are listed.